Edukacyjna rola przewodników o uzdrowiskach galicyjskich w drugiej połowie XIX i na początku XX wieku - Barnaś-Baran, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The article attempts to show the role of the spas as a place of health education and people associated with them, especially spa doctors, in the process of preparing patients for purposeful, conscious and committed treatment. It analyses mainly guidebooks and manuals issued by doctors working in known in the nineteenth and early twentieth century spas, including Krynica, Szczawnica, Iwonicz, Truskawiec. It was determined what were the main thematic areas of their content. Particular attention was paid to the message through which those planning to be treated were educated, as well as people staying in the spa were taught about the norms, regulations and rules of using therapeutic resources. The use of their information, proper attitude and shaping proper pro--health habits was an important element in health education, and above all it brought positive health effects. The guides and manuals were presented and various activities for patients were organized in the spas. They were encouraged to an active lifestyle and proper nutrition. It should be emphasized that it was made clear that after returning from the treatment a healthy lifestyle had to be continued.
Keywords: Galicia; education; health resorts; guides; spa physician